PENGENDALIAN THELAZIASIS PADA TERNAK SAPI DENGAN MENGGUNAKAN REBUSAN DAUN SIRIH DI DESA OEFAFI - Ni Sri Yuliani (Jurnal Pengabdian Masyarakat Peternakan, 2016)
Oefafi village located in East Kupang district, there are two groups of animals: Tun Feu consisting of 5 people and Aim HIF Nao consisted of 6 people. Each member has a tail with 3-5 cattle pasture ± 5 hectares. Endemic disease that infects cattle: Septicemia epizootika and Thelaziasis. Supporting factors: the limited knowledge of farmers on the management of animal health, such as vaccination, sanitation cage. Rotational grazing, cattle feces processing into organic fertilizer and the eradication of the flies as mechanical vectors Thelaziasis not been implemented. Target outcomes: skilled workers formed 50% of the total number of members, in the areas of: vaccination, manufacture neem extract, betel leaf decoction manufacture, processing feces. The presence of a pilot cage every group. Specific target, the target group is expected to be an example for cattle farmers in the province of NTT. Based on observations and information, since the vaccination SE until December 2015 is clinically undiscovered Septicemia epizootika and generated 7 vaccinators. Fly population can be controlled as has been done cage sanitation, rotation grazing, available ± 11 liter extract of neem production (exterminating flies) and the resulting 5 person skilled workers. Thelaziasis incidence decreases gradually because there is a skilled labor 9 in control using betel leaf decoction. There Demplot cage, fertilizer bokasi each group of skilled labor and 4 of the planned target 5 people.       Keywords : Vaccination, Herbs, Bali Cattle